Application of Photogrammetric and The Scanline Survey Approaches for Rock Slope Stability Analysis - Syifaa Nadia Zulkifli; Nurul Ainain Mohd Salim; Diana Che Lat (International Journal of Integrated Engineering, 2025)
The stability of rock slopes in quarries is a critical concern, particularly under the constant threat of collapse due to ongoing blasting activities. These slopes have been assessed and analysed using a variety of approaches, including traditional field surveys and modern remote sensing techniques. Despite advancements, doubts persist regarding the accuracy and reliability of photogrammetry compared to conventional methods, despite its capability to gather vast amounts of data efficiently. This study focused on utilizing both scanline surveys and photogrammetry to gather discontinuity information on rock slopes. An Unmanned Aerial Vehicle (UAV) was employed to capture visual images, from which orientation and discontinuity features were extracted. Agisoft Metashape software facilitated the creation of a detailed 3D point cloud model. Subsequently, CloudCompare was used to process the photogrammetric outputs, enabling geological plane extraction crucial for assessing kinematic stability and identifying major discontinuity sets within the slope. The stability analysis of the rock slope was performed using PLAXIS 3D, employing both the Jointed-Rock and Mohr Coulomb models to determine Factors of Safety (FoS). Structural failure scenarios were simulated by reducing ϕ/c parameters and applying uniform vertical loads. Analysis of dip angle and dip direction data acquired from dense point clouds via the CloudCompare compass plugin demonstrated reliability, with differences of under 20 percent. The findings from scanline surveys and photogrammetry methods indicated comparable stability and a low risk of failure, as indicated by FoS values remaining above the permissible minimum threshold for stability assessment.